X-ray fluorescence-based method for the quantitative determination of uranium in the aqueous solutions; Journal of Physics: Conference Series; Vol. 781 : Nuclear Reactor Physics 2016 (ICNRP-2016) - Dubrovka S. P. Svetlana Pavlovna (2017, 2017)
Title screen